OPTIMALISASI PENJUALAN KUE TRADISIONAL DJAJE DENGAN PENDEKATAN STP - Ismali Marzuki Sianturi (Jurnal Ilmu Komputer Ruru, 2024)
Djaje is a traditional cake business that has been established in 2017. The products sold by Djaje are various wet snacks. The initial strategy used was only offline, such as leaving cakes to resellers, but as the number of competitors increased, Djaje's sales decreased. This study uses a qualitative descriptive method by explaining the results obtained using analysis STP (Segmentation, Targeting, Positioning). The purpose of this study was to determine the results of implementing digital marketing strategies in improving traditional cakes. Results implementation of the implemented strategy by adjusting the content of photos, descriptions, posts, and advertisements using analysis STP (Segmentation, Targeting, Positioning) as a basis. By using various digital platforms to reach more potential consumers, Djaje has succeeded in making cake sales increase in sales from October 2021 to March 2022